Initial social impact of the Rupsha bridge project in Khulna - Murtaza, Mohammad G.; M. Ghulam Sattar (BRAC Research and Evaluation Division (RED), 2019)
Fallowing a decision by the government to construct a bridge over the river Rupsha in Khulna, a number of preparatory studies were undertaken on different aspects of the bridge project. An initial social impact assessment was a part of these studies. Two alternative sites have been considered for the bridge, and for that two alternative alignments of road have been proposed. Construction of the new road(s) would necessitate acquisition of land, involve displacement of people from their existing habitats, and affect these people in other ways both socially and economically. The study found that a total 454 households (174 in alignment A, and 280 in alignment B) would be affected if roads are constructed as per the proposed alignments. The total population involved is 2,571. . .<\round 60 per cent of these people were born in their existing villages, and the rest migrated from other places at different times. The two road alignments pass through periurbanlrural areas where a number of fish farms, small industries and commercial enterprises are located. A very large number of the income earners are involved in ' serivce' and non-farm vocations. Many women are also participating in income earning activities. Most of these people live quite close to their workplace. In the two alignments 45,847 trees will be affected. The findings incorporated some reactions of the people living in the project area. Their major concerns are loss of land including their ancestral homesteads, loss of current occupations and displacement. Some of the respondents even said that they did not need any more road in their locality.